Needs Analysis for English Syllabus Design Based on Natural Approach at Islamic Boarding School - Riska Ramadhani; Dewi Yana; Warno Edi (Green Publisher Indonesia, 2025)
A needs analysis is essential for teachers to develop and identify the appropriate materials for students, as well as to determine the methods and strategies to use in each class. This study aims to find information regarding the student’s needs for English courses at Islamic Boarding School Muhammad Al-Haqqi Batam. The researchers carried out qualitative research. The participants in the study consisted of 14 students. The data collection instruments were in a questionnaire sheet and the form of a short interview. The needs analysis included distributing questionnaires to students to gather information related to the requirements of the English course. The study's findings show that students understand the value of studying English for their future, which motivates them to enhance their English abilities. Syllabuses for English lessons should be modified to coincide with their needs, which allows them to practice English and use their abilities for future success.